Adolescent Religiosity as a Mediator of the Relationship Between Parental Religiosity and Adolescent Health Outcomes - Barton, Alison L. (Journal of religion and health, 2014)
Studies have demonstrated the positive impacts of both parent and adolescent religiosity on adolescent outcomes; however, the relationships among these variable have not been studied. Our study was conducted to assess whether adolescent religiosity mediates the relationship between parent religiosity and adolescent emotional and behavioral health outcomes. A sample of 491 late adolescents ages 18-22 completed surveys that assessed their parents' religious practices, their own religious practices, deviant behaviors, and internalizing behaviors. Findings suggest that adolescent religiosity mediates the relationship between parents' religiosity and adolescent health outcomes such as drug and alcohol use and depression.